Insecticidal and repellent effect of cinnamon oil on flies associated with livestock Efecto insecticida y repelente del aceite de canela sobre moscas asociadas con el ganado - Boito J.P.* (2018)
© 2018 Rev.MVZ Córdoba.Objective. Due to the increased parasitic resistance, there is a need to explore alternative insecticides, including natural products, such essential oils. In this sense, the aim of this study was to evaluate, for the first time, the insecticidal and repellent effect of Cinnamomun zeylanicum (free and nanoemulsion forms) in vitro and in vivo. Materials and methods. For that, the insecticidal effect of the free form was tested at 1.0, 5.0 and 10%, while the nanoemulsion form was tested at 0.5, 1.0 and 5.0% against adult house flies, Musca domestica. For validation of the test, the flies were sprayed with the diluent (water and triton 10%) and with blank nanoemulsion (without C. zeylanicum essential oil). Moreover, in vivo test was performed using cows naturally infested with Haemotobia irritans. Results. The results demonstrated that cinnamon oil (10%) and the nanoemulsion (5%) were 100% effective against M. domestica after 90 minutes of exposure. The repellent effect was tested in vivo using 5% of cinnamon oil on Holstein cows naturally infested by Haemotobia irritans. The flies were counted at 0, 1, 2, 3, 9 and 24 h after cinnamon oil treatment. It was verified significant decrease (p < 0.05) in the number of flies on cows sprayed with cinnamon in all times. Conclusions. Based on these results, C. zeylanicum showed insecticidal effect (in vitro) against domestic flies and repellent effect (in vivo) against the horn fly.© 2018 Rev.MVZ Córdoba.Objetivo. Debido a la mayor resistencia parásita, hay una necesidad de explorar insecticidas alternativos, incluidos los productos naturales, tales como aceites esenciales. En este sentido, el objetivo de este estudio fue evaluar, para el primer equipo, el efecto insecticida y repelente de Cinnamomum zeylanicum (formas libres y nanoemulsión) in vitro e in vivo. Materiales y métodos. Para ello, el efecto insecticida de la forma libre se ensayó a 1.0, 5.0 y 10%, mientras que la forma nanoemulsión se ensayó a 0.5, 1.0 y 5.0% frente a las moscas domésticas adultas, Musca domestica. Para la validación de la prueba, las moscas fueron rociados con el diluyente (agua y triton 10%) y con nanoemulsión en blanco (sin aceite esencial de C. zeylanicum). También, fueron realizados pruebas in vivo usando vacas naturalmente infestadas con Haemotobia irritans. Resultados. Los resultados demostraron que el aceite de canela (10%) y la nanoemulsión (5%) fueron 100% eficaz contra M. domestica después de 90 minutos de exposición. El efecto repelente se ensayó in vivo usando 5% de aceite de canela en vacas Holstein, naturalmente infestados por Haemotobia irritans. Se contaron las moscas a las 0, 1, 2, 3, 9 y 24 h después del tratamiento el aceite de canela. Se verificó disminución significativa (p < 0.05) en el número de moscas vivas de vacas canela pulverizada en todo momento. Conclusiones. En base a estos resultados, C. zeylanicum mostró un efecto insecticida (in vitro) contra las moscas domésticas y efecto repelente (in vivo) contra la mosca de los cuernos.